GSDME and its role in cancer: From behind the scenes to the front of the stage. Issue 12 (8th December 2020) - De Schutter, Elke; Croes, Lieselot; Ibrahim, Joe; Pauwels, Patrick; Op de Beeck, Ken; Vandenabeele, Peter; Van Camp, Guy
Abstract: Gasdermin E (GSDME), a gene originally involved in hereditary hearing loss, has been associated with several types of cancer in the last two decades. Recently, GSDME was identified as a pore‐forming molecule, which is activated following caspase‐3‐mediated cleavage resulting in so‐called secondary necrosis following apoptotic cell death, or in primary necrotic cell death without an apoptotic phase, so‐called pyroptosis‐like. This implication in cell death execution suggests its potential role as a tumor suppressor. GSDME also exhibited a cancer type‐specific differential methylation pattern between tumor tissues and normal cells, implying GSDME gene methylation as both a pan‐cancer and cancer type‐specific detection biomarker. A bit paradoxically, GSDME protein expression is considered to be less suited as biomarker, and although its ablation does not protect the cell against eventual cell death, its protein expression might still operate in tumor immunogenicity due to its capacity to induce (secondary) necrotic cell death, which has enhanced immunogenic properties. Additionally, GSDME gene expression has been shown to be associated with favorable prognosis following chemotherapy, and it could therefore be a potential predictive biomarker. We provide an overview of the different associations between GSDME gene methylation, gene expression and tumorigenesis, and explore their potential use in the clinic. Our review only focuses on GSDME and summarizes the current knowledge and most recent advances on GSDME 's role in cancer formation, its potential as a biomarker in cancer and on its promising role in immunotherapies and antitumor immune response.